Shape analysis of the basioccipital bone in Pax7-deficient mice. Issue 1 (December 2017) - Cates, Joshua; Nevell, Lisa; Prajapati, Suresh; Nelon, Laura; Chang, Jerry; Randolph, Matthew; Wood, Bernard; Keller, Charles; Whitaker, Ross
Abstract We compared the cranial base of newbornPax7 -deficient and wildtype mice using a computational shape modeling technology called particle-based modeling (PBM). We found systematic differences in the morphology of the basiooccipital bone, including a broadening of the basioccipital bone and an antero-inferior inflection of its posterior edge in thePax7 -deficient mice. We show that thePax7 cell lineage contributes to the basioccipital bone and that the location of thePax7 lineage correlates with the morphology most effected byPax7 deficiency. Our results suggest that thePax7 -deficient mouse may be a suitable model for investigating the genetic control of the location and orientation of the foramen magnum, and changes in the breadth of the basioccipital.